Pengembangan Poster Anatomi Tubuh Manusia Berbantuan Augmented Reality (AR) pada Materi Sistem Endokrin Manusia bagi Peserta Didik di SMA Negeri 1 Suwawa - Mangge, Aditya Z.; Mardin, Herinda; Akbar, Muh. Nur; Latjompoh, Masra; Solang, Margaretha (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the level of validity and practicality of human anatomy posters assisted by Augmented Reality (AR) on the human endocrine system material for students at SMA Negeri 1 Suwawa. This study is a type of research and development (R&D) with the ADDIE model, which includes three stages: Analyze, Design, and Develop. Data collection instruments consist of validation sheets from media experts and material experts, as well as teacher and student response questionnaires. The results of the study indicate that the developed learning media obtained a validity percentage from media experts of 93% with a very valid category, while from material experts it was 62.22% with a valid category. The practicality test showed a teacher response of 100% and a student response of 90%, both of which are included in the very practical category. These findings indicate that AR-assisted human anatomy poster media is suitable for use in biology learning, because it is able to facilitate students in understanding the concept of endocrine system anatomy visually and interactively. The implication of this research is that AR-based media can be an innovative alternative for biology teachers in developing 21st-century learning that emphasizes visualization, interactivity, and students' conceptual understanding.